Exploring the Types and Categories of Culture in Algerian Official Exam: The Case of Literary and Foreign Languages Stream Texts in English Baccalaureate Exams from 2005 to 2021 (مجلة الواحات للبحوث والدراسات, 2025)
This descriptive study intends to investigate the types and categories of culture by conducting a content analysis on the texts of 31 foreign languages stream BAC exams from 2005 to 2021. The findings reveal that all analysed texts are designed within a cultural dimension. However, the majority of the texts tend to discuss themes from Big C culture and neglect the small C aspect of culture. Furthermore, the source culture was largely marginalized. Recommendations were provided to make an equilibrated cultural dimension of BAC exam texts.Keywords: Content Analysis, BAC Exam, Culture Types, Culture Categories, Culture and Language